O encontro entre a educação formal e não formal no Programa Escola Integrada: possibilidades e desafios - Luana Campos e Silva (2015)
Partnerships between NGOs and public schools have grown sharply in Brazil. In Belo Horizonte, the Integrated School Program - PEI is an example of public policy which proposes to build partnerships between schools and existing projects, thus indicating a meeting between the formal and non-formal education. In this scenario, this study investigates how was the process of building the partnership between NGOs and the PEI and what changes occur in the educational practices of an NGO when it starts operating in a program developed in formal school. Thus, through interviews and participant observation, this work staked out what elements are close and which are distant educational practices developed at school and how these similarities and differences are articulated in order to expand educational opportunities in connection Integral Education. Analyses of the data indicate that the frequency of children in the project, the working conditions of the subjects of the NGO and the school, the relationship built between educator and student, autonomy, forms of participation, the relationship with the (in) discipline, dialogicity and interfaces with family and community are some points that appear, both in terms of tensions and in terms of progress and possibilities.